(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Nursing programs in vocational high schools expect their graduated to partake in providing care-giving service for the elderly, namely giving professional assistance for individuals or groups of people who cannot take care of themselves in some or all their activities because of physical and/or mental disabilities. This research aimed to redesign nursing skills programs so as to provide graduates able to become competent caregivers. This descriptive research method using qualitative approach was conducted at Public Vocational High School (PVHS), Indonesia. The results showed that the redesign of nursing program can be developed through preparing competent teachers and tutors from industries, providing technical training for students, and creating the academic curriculum of caregiver competencies. The preparation of competent teachers can be done by establishing industry-certified internship programs for teachers and providing them with some training. The tutor preparation was done by redesigning the curriculum becoming the convergent curriculum which combines the subject matters at the competencies of nursing and caregiver programs for the elderly. The training for students is given by online and offline for 2 months. Eventually, it can be concluded that the convergent curriculum for nursing and caregivers will provide graduated with a standard competency for being better caregivers.